Kesan ekonomi pelancongan terhadap komuniti batek di Kuala Tahan, Pahang - Zanisah Man,; Nurul Fatanah Zahari,; Mustaffa Omar, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2009)
Tourism plays an important role in generating employment and income opportunities for the Batek community living near the National Park, Pahang. This article seeks to explore into the issues and challenges faced by Batek community as a result of tourism industry development in Kuala Tahan. Pahang. In this context, the Batek community is no exception to receive spill over effects from the development of this industry. Their involvement in the tourism economy in Taman Negara, Pahang can be divided into two categories: as an employee (tour guide and boat driver) as well as subject to tourist attractions in its own (cultural icons). Batek women, especially in Kg. Gua Telinga and Kg. Dedari also participate in the economy as producers of handicrafts with men to help market the product. However, Batek community involvement in the tourism industry, either as tour guide and/or boat driver depends by and large on good relations with the outside community, as well as their ability to communicate well when dealing with foreign tourists. Tourism also has some impact on the Batek community. It does interfere with the individuals and communities privacy rights, the rights of the community in maintaining cultural authenticity, limiting the freedom of movement in finding their source of livelihood, increase potential threats in health and disease from outside, increasing demand for better quality products for the market, and finally increased competition and exploitation of resources from external forces